Treatment options of human demodicosis - Olga Pawełczyk (Journal of Education, Health and Sport)
Background: Human demodicosis is a parasitic disease caused by two species of mites, Demodex folliculorum and Demodex brevis. Cutaneous and ocular demodicosis most often occurs in a situation of impaired immune response, where the attacked organism is weakened, has reduced immunity or metabolic disorders. The treatment of demodicosis can last up to several months and requires a lot of patience and regularity from the patient.